(untitled) (Książnica Śląska, 2025)
The article recalls the figure of Jerzy Ronard Bujański, an actor, director, radioman and writer. The text describes materials from his legacy, collected in the Special Collections of the Silesian Library in Katowice. The Bujański’s artistic archive contains interesting materials: his typescripts, including theatrical studies, memoirs, scenic works (dramas, opera and ballet librettos), radio and literary texts (both prose and poetry). The author of the article characterizes the previously unknown work of Bujański and discusses it in terms of themes, problems and genres. This article supplements the biography of Jerzy Ronard Bujański and provides information about his unknown and unprinted texts and works.